Debenzylation of Functionalized 4- and 5-Substituted 1,2,3-Triazoles - Farooq, Tahir; Sydnes, Leiv K.; Törnroos, Karl W.; Haug, Bengt Erik (Synthesis, 2012)
A range of 4- and 5-substituted N-benzyl-1,2,3-triazoles have been submitted to debenzylation using Pd/C and hydrogen in the presence of 1,1,2-trichloroethane. Triazoles with oxygen-containing substituents are efficiently debenzylated under these conditions. Triazoles with a phenyl or benzyl substituent on C4 or C5 are not debenzylated, whereas a pentyl-substituted derivative was readily debenzylated.
Keywords: hydrogenolysis; triazoles; alkynes; debenzylation; dehydrochlorination